2017
DOI: 10.1002/pon.4335
|View full text |Cite
|
Sign up to set email alerts
|

Cycles of silence: First Nations women overcoming social and historical barriers in supportive cancer care

Abstract: Widespread silence around cancer reflects both the limited access First Nations people have to formal, supportive programs and services, as well as the creative ways they provide emotional, social, and financial support within their informal networks. Beyond the support of their communities, they also required institutional provision of care that is culturally safe, addressing the colonial impacts on cancer communication and the disproportionate burdens of disease in First Nations communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 31 publications
2
59
0
Order By: Relevance
“…This study builds on our foundational studies which overwhelmingly identified a gap in the delivery of culturally safe cancer survivorship support for First Nations and Métis people [18, 20–24]. One of the first opportunities to voice their survivorship experiences, our first study (funded by Canadian Cancer Society), highlighted the profound failures of healthcare services to recognize the distinct ethnic, cultural, and socio-historical positioning of First Nations and Métis people.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study builds on our foundational studies which overwhelmingly identified a gap in the delivery of culturally safe cancer survivorship support for First Nations and Métis people [18, 20–24]. One of the first opportunities to voice their survivorship experiences, our first study (funded by Canadian Cancer Society), highlighted the profound failures of healthcare services to recognize the distinct ethnic, cultural, and socio-historical positioning of First Nations and Métis people.…”
Section: Introductionmentioning
confidence: 98%
“…One of the first opportunities to voice their survivorship experiences, our first study (funded by Canadian Cancer Society), highlighted the profound failures of healthcare services to recognize the distinct ethnic, cultural, and socio-historical positioning of First Nations and Métis people. It revealed that stigmatization, fear of disclosing cancer, and culturally insensitive healthcare approaches prevent Indigenous people from receiving survivorship care, including follow-up and regular monitoring for early detection and survivorship interventions for enhancing quality of life [21, 22, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognised that, as with health services in general, there is a lack of culturally appropriate cancer services to engage Indigenous peoples. Fear or lack of trust of mainstream health facilities, lack of understanding or respect being shown by health care providers, poor communication by health care providers, fatalistic or differing cultural beliefs about cancer, and logistical difficulties in accessing screening and treatment services have been identified as inhibiting Indigenous people’s engagement with cancer care [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. It has been noted that attention should focus on how cancer service providers deliver services to their Indigenous patients and on ways in which they can improve to better meet the needs of Indigenous peoples [ 12 , 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear or lack of trust of mainstream health facilities, lack of understanding or respect being shown by health care providers, poor communication by health care providers, fatalistic or differing cultural beliefs about cancer, and logistical difficulties in accessing screening and treatment services have been identified as inhibiting Indigenous people’s engagement with cancer care [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. It has been noted that attention should focus on how cancer service providers deliver services to their Indigenous patients and on ways in which they can improve to better meet the needs of Indigenous peoples [ 12 , 13 , 17 ]. In Australia, the National Aboriginal and Torres Strait Islander Cancer Framework has identified that “culturally safe services and a culturally competent workforce… are core requirements for improving cancer outcomes” [ 19 ] (p. 15), highlighting the essential role that cancer service providers have in encouraging and maintaining Indigenous Australians’ attendance at cancer services to gain the benefits of modern cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural safety is an approach to delivering care that is based on establishing trusting and reciprocal relationships between a patient and their healthcare provider [49]. Lack of culturally safe care has been noted to be a barrier to accessing cancer care among FN people [34, 45, 50, 51]. Racism, discrimination, and fear of judgment have been noted to impede access to both primary care [37, 38] and cancer care [32, 47, 50, 52, 53], by causing patients to delay or avoid accessing care.…”
Section: Discussionmentioning
confidence: 99%